Physiotherapy for Parkinson's Disease in Sweden: Provision, Expertise, and Multi‐professional Collaborations. Issue 6 (20th August 2017) - Conradsson, David; Leavy, Breiffni; Hagströmer, Maria; Nilsson, Maria H.; Franzén, Erika
Abstract: Background: Evidence for the positive effects of physiotherapy for persons with Parkinson's disease (PwPD) is rapidly increasing. However, little is known about the provision of physiotherapy for PwPD in everyday practice. The objective of this study was to gain insight into the nature of physiotherapeutic care for PwPD in hospitals, primary care units, and community services in Sweden. Methods: A web‐based survey was sent out to 2956 members of the Swedish Association of Physiotherapists, including questions about treatment, measurement tools, multi‐professional collaborations, adherence to physiotherapy guidelines, professional expertise, and needs for gaining expertise regarding PwPD. Results: Of the 1189 physiotherapists who completed the survey, 705 were treating 1 or more PwPD per month in hospitals (21%), in primary care units (37%), and in the community (42%). Physiotherapy frequently targeted a wide range of musculoskeletal and mobility impairments; however, freezing of gait and pain were less frequently treated. Measurement tools recommended for PwPD were infrequently used, and there was a preference for single‐item questions/tools compared with multi‐item instruments. Collaboration with other health care professionals for the rehabilitation of PwPD was rare and was more evident in hospitals than in primary care units and the community. Adherence to physiotherapy guidelines was poor, and most respondents reported that they treated too few PwPD to retain their expertise and they perceived a need to increase their knowledge and skills about physiotherapy for PwPD. Conclusion: The current findings emphasize the need to strengthen expertise regarding the assessment and treatment of PwPD among physiotherapists in Sweden and to apply strategies endorsing multi‐professional collaboration for PD rehabilitation.